Tuning the microstructure and metastability of β-Ti for simultaneous enhancement of strength and ductility of Ti-based bulk metallic glass composites - Zhang, Lili T. (2021)
A parametric experimental study on the role played by the size, metastability, and volume fraction of the dendritic β-Ti phase on the tensile properties of amorphous matrix composites is conducted. Towards this end, several bulk metallic glass composites (BMGCs) with varying compositions were synthesized, processed under different cooling rates and tensile tested. Results show that the stress induced martensitic transformation, from β to α″, of the dendritic Ti phase enhances the resistance to shear band propagation and, in turn, imparts significant strain hardening capability to the composite. This transformation was found to be favored in BMGCs in which the size of the dendrites is relatively coarse and Co content is ∼1 at.%. Furthermore, a volume fraction of the dendritic phase between 34% and 45% was found to result in optimum combination of strength and ductility. The utility of these microstructural design principles learned from this study was demonstrated by design, synthesis, and testing of a BMGC containing transformable β-Ti with a volume fraction of ∼38% that simultaneously exhibits high strength and ductility.